Association between organophosphate esters exposure and the prevalence of hyperuricemia in US adults from NHANES 2011–2016 - Qiong Huang; Wenbin Nan; Siqi Li; Baimei He; Xu Cai; Zhenyu Peng; Chenlu Wu (Scientific Reports)
Abstract Organophosphate esters (OPEs) exposure has potentially harmful effects on human health. However, the evidence between OPEs and hyperuricemia is insufficient. We aimed to assess the association between OPEs metabolites and the prevalence of hyperuricemia. Multivariable logistic regression, weighted quantile regression (WQS) model, and Bayesian kernel machine regression (BKMR) models were used to investigate the association of OPEs metabolites with the risk of hyperuricemia. Mediation analysis was conducted to assess whether inflammation mediated the effects of OPEs on the prevalence of hyperuricemia. The multivariable logistics regression indicated that bis (1,3-dichloro-2-propyl) phosphate (BDCPP) and bis-2-chloroethyl phosphate (BCEP) were positively correlated with the risk of hyperuricemia. In WQS and BKMR analyses, OPEs mixtures presented a positive association with the risk of hyperuricemia, with BDCPP being the primary contributor. C-reactive protein (CRP) and monocytes were found to mediate the association between BDCPP and the risk of hyperuricemia prevalence, with 8.46% and 3.97% of the mediated proportion, respectively. Our study revealed that OPEs mixtures were positively correlated with the prevalence of hyperuricemia, with BDCPP identified as the most significant contributor. Inflammation was a potential mechanism mediating the effect of BDCPP exposure on the risk of hyperuricemia.